Colostrum Feeding Myth and Science in Buffalo Calf Management - Kumar, Santosh; Deb, S M; Madkar, A R; Chandra, Ramesh; Borah, BKD (Indian Farming, 2016)
Colostrum is nectar for improvement of immune deficiency in newly born buffalo’s calf. Colostrum feeding not only helps to grow faster, mature early, but save from several pathogenic as well as deficiency diseases. Several misconceptions prevail about colostrum feeding to newly born calf and need to be removed for raising of healthy calf.